Does hydrogen-rich water mitigate MP toxicity in rainbow trout (Oncorhyncus mykiss)? Monitoring with hematology, DNA damage, and apoptosis via ROS/GSH/MDA pathway - Atamanalp Muhammed; Kırıcı Muammer; Köktürk Mine; Kırıcı Mahinur; Alwazeer Duried; Kocaman Esat Mahmut; Ucar Arzu; Parlak Veysel; Özcan Sinan; Alak Gonca (Oceanological and Hydrobiological Studies)
Although the number of studies documenting the presence of Microplastics (MP) in fish is increasing, research studies focused on its detoxification are very limited. In this study, rainbow trout (Oncorhyncus mykiss) were randomly divided into two groups after being fed with MPs (15% polypropylene [PP] +15% polyethylene [PE]) for 2 months. MP excretion without any application (PP+PE) in group I fish, and excretion of MPs with hydrogen-rich water (HRW) application (PP+PE+HRW) in group 2 were investigated under semi-static conditions for 21 days. This effect was also compared by using positive and negative control groups (Control [no treatment, free PP, PE or/and HRW] and only HRW group). In this direction, the following were determined: PP+PE chronic toxicity in aquatic organisms, the toxicity mechanism and the effect of HRW as a possible treatment method in blood tissue; with hematological indices ([RBC count [RBC], leukocyte count [WBC], hemoglobin value [Hb], hematocrit ratio [Hct], platelet count [PLT], hemoglobin count per erythrocyte [MCHC], mean hemoglobin amount per erythrocyte [MCH] and mean erythrocyte volume [MCV]) in other tissues (liver, gill and brain tissue) oxidative stress response (catalase [CAT]), glutathione peroxidase (GPx), glutathione reductase (GR), superoxide dismutase (SOD), glutathione (GSH), reactive oxygen products (ROS), malondialdehyde ([MDA] levels), DNA damage (8-OHdG: 8-Hydroxy-2-Deoxyguanosine), and the apoptosis (caspase 3) levels were investigated. In addition, acetylcholinesterase enzyme (AChE) activity, which is important in neurotoxicity pathways in the brain, was determined. The presence of plastics (PP/PE) in target tissues (muscle, liver, gill and gastrointestinal tract) was also obtained.